Guidelines for reporting health research: what authors should check before submitting an article - Sharma, Apurb; Aryal, Diptesh (Journal of Society of Anesthesiologists of Nepal, 2016)
With the publication of the 2016 September issue, Journal of Society of Anesthesiologists of Nepal (JSAN) has published its revised instruction to authors. The editorial board of JSAN has taken all possible steps to ensure the quality of the material published in the journal remains high and advise the authors to use the minimum set of items needed for a complete and clear description of the research methodology, findings of the study and discussion of the results. The new instructions to authors abide by the recommendations of the Equator Network and guide the authors to follow the checklists and guidelines to report their findings.